Comparison of temporomandibular joint and ramus morphology between class II and class III cases before and after bi-maxillary osteotomy. Issue 12 (December 2017) - Iguchi, Ran; Yoshizawa, Kunio; Moroi, Akinori; Tsutsui, Takamitsu; Hotta, Asami; Hiraide, Ryota; Takayama, Akihiro; Tsunoda, Tatsuya; Saito, Yuki; Sato, Momoko; Baba, Nana; Ueki, Koichiro
Abstract: Purpose: The purpose of this study was to compare changes in temporomandibular joint (TMJ) and ramus morphology between class II and III cases before and after sagittal split ramus osteotomy (SSRO) and Le Fort I osteotomy. Materials and methods: The subjects were 39 patients (78 sides) who underwent bi-maxillary surgery. They consisted of 2 groups (18 class II cases and 21 class III cases), and were selected randomly from among patients who underwent surgery between 2012 and 2016. The TMJ disc tissue and joint effusion were assessed by magnetic resonance imaging (MRI) and the TMJ space, condylar height, ramus height, ramus inclination and condylar square were assessed by computed tomography (CT), pre- and post-operatively. Results: The number of joints with anterior disc displacement in class II was significantly higher than that in class III (p < 0.0001). However, there were no significant differences between the two classes regarding ratio of joint symptoms and ratio of joint effusion pre- and post-operatively. Class II was significantly better than class III regarding reduction ratio of condylar height (p < 0.0001) and square (p = 0.0005). Conclusion: The study findings suggest that condylar morphology could change in both class II and III after bi-maxillary surgery. The findings of the numerical analysis also demonstrated that reduction of condylar volume occurred frequently in class II, although TMJ disc position classification did not change significantly, as previously reported.